Profiles of Plasminogen Activator Inhibitor-1 Levels in Healthcare Workers with Latent Tuberculosis and Non-Latent Tuberculosis Infections (Healthy Control) - Tonapa, Sanrio Neuro; Ahmad, Nur; Saleh, Sahyuddin; Bakri, Syakib; Minhajat, Rahmawati; Akil, Fardah; Seweng, Arifin (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Mycobacterium tuberculosis infection causes the release of proinflammatory cytokines; interleukin IL-1, IL-6, and IL-8, as well as tumor necrosis factor (TNF-α), affecting hemostasis, namely an increase in procoagulation activity, a decrease in anticoagulant factors, and suppression of the fibrinolytic system that causes hypercoagulable states. Methods: This is a cross-sectional study that involves 80 healthcare workers. The study was conducted in two academic medical centers that were part of the healthcare system of Makassar city, South Sulawesi province, Indonesia, from September to October 2021. PAI-1 levels were measured using the enzyme-linked immunosorbent assay technique. The statistical test results were significant if the p values were <0.05. Results: Although there was no statistically significant difference (P > 0.05) in PAI-1 levels, PAI-1 level among participants in the LTBI group was found to be lower (4.9 ng/mL) than in the healthy control group (6.0 ng/mL). In addition, participants in the LTBI group with a history of being infected (9.6 ng/mL) with the COVID-19 had higher PAI-1 levels than those who had never been infected (2.3 ng/mL), which is statistically significant (P = 0.004). Although there was no statistically significant difference (P > 0.05) in PAI-1 levels among participants in the healthy control group, those with a history of being infected (6.7 ng/mL) demonstrated higher PAI-1 levels than those who had never been infected (4.8 ng/mL). Conclusions: PAI-1 levels were lower in LTBI participants than in healthy control participants, which potentially is due to more participants in the healthy control group having a history of COVID-19 infection.